Diseño de un equipamiento urbano de atención en servicios públicos en el barrio “10 de agosto”, Ibarra - Benavides Amaya, Kevin Fernando (2024)
The city of Ibarra, located in the northern highlands of Ecuador, has experienced significant population growth in recent decades, resulting in urban expansion towards the periphery of the city, particularly in the southern area. This expansion is driven by the high feasibility of land use for the creation of new residential zones that can meet the housing demand of new residents. This urban growth has led to various challenges regarding access to services and the fulfillment of daily needs. The distances between residential areas and essential services are increasingly long, leading to higher economic investment due to the increased use of both public and private transportation. Time spent on commuting is also growing due to severe traffic congestion when entering and leaving the city center, where most public services and facilities are located. The quality of public and private institutional services is subpar, as there is an imbalance between supply and demand, with a greater number of users and fewer service windows, among other difficulties. Through methodological tools such as mapping existing facilities, measuring accessible distances between points A and B, analyzing coverage networks, collecting demographic data, and conducting semi-structured interviews, the real state of the problem was identified, along with the most urgent issues to be addressed according to the population and all direct stakeholders. These issues include the need for increased public safety, the proper balance of consolidated or consolidating urban environments, and easy access to public services for the general population. As a result, the design of a public services facility is proposed for the 10 de Agosto neighborhood, with the main objective being the integration of mixed-use services, including financial, administrative, commercial, and public safety services within a single facility, thereby facilitating access to public service management and coverage.